Bacterial contamination of nasogastric feeding tube and development of neonatal sepsis in premature newborns: a prospective observational research at a tertiary care center in Gujarat, India - Thaddanee, Rekha; Morbiwala, Shamim; Chauhan, Hasmukh; Gusani, Jigar; Dalal, Parima (International Journal of Contemporary Pediatrics, 2018)
Background: The objective of the present study is to observe the effect of frequency of changing nasogastric feeding tube (NG-FT) on microbial growth in relation to development of neonatal sepsis in premature newborns. The study is prospective observational study in its nature. Neonatal intensive care unit (NICU) of a tertiary care teaching hospital of western Gujarat, India, from December 2016 to November 2017. Methods: Eighty-five preterm newborns admitted to NICU for feeding support were randomly divided into three groups depending on frequency of changing nasogastric feeding tubes (Group I, II and III with NG-FT changed every 12, 24 and 48 hourly respectively). In Groups I, II and III, the first NG-FT cultures were sent at the end of 12, 24, 48 hours of NG-FT insertion respectively. The second and third NG-FT cultures were sent after 7 and 14 days respectively. Microbial growth pattern was observed and correlated with development of necrotizing enterocolitis (NEC), neonatal sepsis and mortality. Results: Microbial growth on first NG-FT culture significantly increased when frequency of changing nasogastric feeding tube was reduced from every 12 to 24 or 48 hours p = 0.0432 (Group I vs II) and 0.0001 (Group I vs III). Microbial growth increased on second (24.1%, 87% and 85% in groups I, II and III respectively) and third NG-FT culture (44% in group I and 100% in groups II and III); this was significantly high in group II and III as compared to group I (p = 0.0001). Common organisms isolated were Klebsiella pneumonia (63.28%), Pseudomonas aeruginosa (32%) and Escherichia coli (21%). No significant difference was noted in incidences of feeding intolerance, necrotizing enterocolitis (NEC), neonatal sepsis and mortality among the three groups. Conclusions: Organism growth in nasogastric feeding tube culture increases significantly when frequency of changing NG-FT is beyond 12 hours. However, there is no increase in episodes of feeding intolerance, necrotizing enterocolitis (NEC), neonatal sepsis and mortality.